(untitled) (Letras, 2019)
From the epistemological framework of interdisciplinarity between literature, aesthetics and theology article suggests thinking of theological aesthetics in a relational circularity, since the mystical key to nuptiality as the current home of the expectation of you. To test this hypothesis, the article is divided into two parts: the first develops the theoretical fundamentals of nuptiality as a dynamic center of theological aesthetics located in the postmodern context of the expectation of the other; in the second, the applicability of the canonical poetic figure in the center is shown from the figures derived from expectation, home and nuptiality.